Risk factors for metabolic syndrome in medical faculty students of HKBP Nommensen University - David Mangarahon T Simangunsong; Ade Maria Sibarani (Science Midwifery, 2023)
Metabolic syndrome is a set of metabolic conditions associated with central obesity, increased blood pressure, decreased glucose tolerance, insulin resistance, increased triglycerides and LDL cholesterol. The World Health Organization states that cardiovascular diseases (stroke, coronary heart disease), which are manifestations of metabolic syndrome, are the number one cause of death in the world. Indonesia itself is experiencing an increasing prevalence of metabolic syndrome, especially in children and adolescents, which is caused by poor lifestyle. This study aims to identify cardiometabolic risk factors in students of the Faculty of Medicine, HKBP Nommensen University. This study is descriptive with a cross-sectional design. Data were collected by interview, questionnaire, and anthropometric measurements. Data were analyzed by descriptive test. The results showed that the majority of the nutritional status of the students of the Faculty of Medicine of HKBP Nommensen University was obesity (38.3%), smoking habits (1.7%), lack of exercise (62.1%), the average duration of sleep of students at the Faculty of Medicine of HKBP Nommensen University was about 6.1 hours per day. The average screen time was about 7.3 hours for cell phones, one hour for tablets, 0.9 hours for laptops, and 2.75 hours for video games. A total of 66.7% of respondents had unhealthy food consumption habits, with an average frequency of consumption of 2 times per week. Further research is needed by examining biochemical profiles and looking at other metabolic risk factors.